United States Concepts of Due Process in Criminal Procedure and the International Criminal Court - Swenson, Delaine Russell (Review of European and Comparative Law, 2025)
The provisions of the Rome Statute of the International Criminal Court should be evaluated considering the due process principles of the United States Constitution to determine if it would be appropriate for the US government to sanction the sending of a US citizen to the ICC or adopting the Rome Statute. There are several areas including the right to trial by jury, right to confrontation, speedy trial and the composition of the Court that raise serious due process concerns from an American perspective. Considering the ICC’s inability to guarantee the same due process protected by the US Constitution there are serious doubts about American involvement in the Court.